OUTCOMES OF ECO‑SUSTAINABLE PRISON INFRASTRUCTURE IN INDIA: RESOURCE CONSERVATION, WASTE MANAGEMENT, AND SOCIOECONOMIC EFFECTS - Ojha, Lallan; Dubey, Arunanshu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Indian correctional institutions face increasing pressure due to overcrowding, high resource consumption and environmental degradation. Integrating environmental protection measures within prison infrastructure offers an opportunity to promote ecological sustainability while contributing to socioeconomic development. This study examines eco-sustainable initiatives in Indian prisons, focusing on resource conservation, waste management systems, renewable energy adoption and water efficiency measures. The analysis highlights how green prison reforms reduce operational costs, minimise environmental footprints and enhance rehabilitation outcomes through skill development and environmental awareness among inmates. Case-based observations from selected Indian states demonstrate the potential of sustainable correctional facilities to contribute to national environmental goals and the Sustainable Development Agenda. The findings suggest that eco-sustainable prison infrastructure not only supports environmental protection but also fosters long-term socioeconomic benefits through employment generation, reduced recidivism and improved public health outcomes. Policy recommendations are proposed to strengthen environmental governance in correctional institutions